2019
DOI: 10.1108/f-08-2018-0101
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to “green operation” of commercial office buildings

Abstract: Purpose The built environment is a major source of carbon emissions. However, 80 per cent of the damage arises through the operational phase of a building’s life. Office buildings are the most significant building type in terms of emission-reduction potential. Yet, little research has been undertaken to examine the barriers faced by building operators in transitioning to a green operation of the office buildings in their care. This study aims to identify those barriers. Design/methodology/approach Building f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
27
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 52 publications
5
27
0
Order By: Relevance
“…In this regard, various studies have reported the barriers to implement SC practices in the context of different countries. The vast majority of the studies (Häkkinen and Belloni 2011;Ahn et al 2013;Durdyev et al 2018a, b;Ogungbile and Oke 2019;Rock et al 2019), particularly from developing countries, reported that concerns with the cost premium of SC and lack of knowledge and awareness are the most significant barriers, which ultimately lead to the reluctance to implement the SC concept. No doubt, that SC will significantly improve economic and social conditions of people as well as reduce the environmental impact of the industry (Mahdiyar et al 2019).…”
Section: Identification Of Drivers and Barriersmentioning
confidence: 99%
“…In this regard, various studies have reported the barriers to implement SC practices in the context of different countries. The vast majority of the studies (Häkkinen and Belloni 2011;Ahn et al 2013;Durdyev et al 2018a, b;Ogungbile and Oke 2019;Rock et al 2019), particularly from developing countries, reported that concerns with the cost premium of SC and lack of knowledge and awareness are the most significant barriers, which ultimately lead to the reluctance to implement the SC concept. No doubt, that SC will significantly improve economic and social conditions of people as well as reduce the environmental impact of the industry (Mahdiyar et al 2019).…”
Section: Identification Of Drivers and Barriersmentioning
confidence: 99%
“…Similar studies from developing countries arrived at the same conclusion, namely, that a lack of knowledge and awareness is the most significant factor impeding sustainability implementation and eventually leads to insufficient sustainability practices (Rock et al, 2019;Bonsu et al, 2019). Furthermore, the study of Amiril et al (2017) found lack of training and education to be the second major barrier to sustainability practices in a Malaysian railway project, leading to slow implementation of sustainable construction practices.…”
Section: Lack Of Knowledge and Standardsmentioning
confidence: 72%
“…The main key for sustainable practice is to minimize environmental impact and costs while maximizing occupant comfort and satisfaction. The need for enhancing corporate and organizational image are also motivators for management to go green (Fauzi et al, 2021;Rock et al, 2019). Hopkins et al (2017) acknowledge and divide the various benefits of sustainability into three perspectives.…”
Section: Literature Reviewmentioning
confidence: 99%